2009
DOI: 10.1186/1471-2393-9-s1-s3
|View full text |Cite
|
Sign up to set email alerts
|

Reducing stillbirths: behavioural and nutritional interventions before and during pregnancy

Abstract: Background: The vast majority of global stillbirths occur in low-and middle-income countries, and in many settings, the majority of stillbirths occur antenatally, prior to the onset of labour. Poor nutritional status, lack of antenatal care and a number of behaviours increase women's risk of stillbirth in many resource-poor settings. Interventions to reduce these risks could reduce the resulting burden of stillbirths, but the evidence for the impact of such interventions has not yet been comprehensively evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 105 publications
1
85
1
1
Order By: Relevance
“…[19][20][21][22][23][24] Probably contributing to the decline, but with little evidence in the literature, is the reduction in stillbirths associated with uterine hyperstimulation, which occurs in the setting of aggressive attempts at labor induction or augmentation. Folic acid food fortification has reduced some congenital anomaly-associated stillbirths, 25 as has ultrasound screening for anomalies followed by pregnancy termination prior to 20 weeks. 24 Fetal monitoring for distress both in the antepartum and intrapartum periods along with the availability of rapid delivery for fetuses in distress or with conditions, such as placental abruption or eclampsia, usually by cesarean section, also contributed to lower stillbirth rates.…”
Section: Stillbirth History In High-income Countriesmentioning
confidence: 99%
“…[19][20][21][22][23][24] Probably contributing to the decline, but with little evidence in the literature, is the reduction in stillbirths associated with uterine hyperstimulation, which occurs in the setting of aggressive attempts at labor induction or augmentation. Folic acid food fortification has reduced some congenital anomaly-associated stillbirths, 25 as has ultrasound screening for anomalies followed by pregnancy termination prior to 20 weeks. 24 Fetal monitoring for distress both in the antepartum and intrapartum periods along with the availability of rapid delivery for fetuses in distress or with conditions, such as placental abruption or eclampsia, usually by cesarean section, also contributed to lower stillbirth rates.…”
Section: Stillbirth History In High-income Countriesmentioning
confidence: 99%
“…No que se refere aos cuidados primordiais, evidências revelam que o controle e tratamento de infecções urinárias, HIV, sífilis, malária, verminoses e doença periodontal durante gestação podem reduzir o risco de óbito fetal 7 . Além disso, o diagnóstico precoce, monitoramento e tratamento da hipertensão arterial e do diabetes mellitus, somados ao acompanhamento dos sinais fetais, suplementação alimentar com ácido fólico, ferro, vitamina A, cálcio e magnésio, são evidências de que cuidados médicos podem reduzir o risco da mortalidade perinatal 7,8,9 .…”
Section: Introductionunclassified
“…Although the issue is definitely under-researched, systematic review of four studies 9 on the effect of indoor air pollution from biomass cooking smoke on pregnancy showed a 51% increase in risk of stillbirth for pregnant women exposed to the pollutants (Pope et al 2010, Yakoob et al 2009). One study in India showed that women cooking with biomass fuels (wood, animal dung or crop residues) were twice as likely to have experienced two or more stillbirths as those using cleaner fuels, like electricity, liquid petroleum gas, biogas or kerosene (Mishra et al 2005).…”
Section: Stillbirthsmentioning
confidence: 99%